(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2022)
The peach belongs to the Rosaceae family; it is a drupe very much desired for its pleasant taste and nutritional qualities, as in the food industry. The peach seed, like other fruits, is rich in oils, phenolic compounds, as well as having a high content of unsaturated fatty acids, which make it very useful for the food industry. In the present work some quality indices of the oil extracted from the seed were determined. The fatty acid composition was determined by gas chromatography with a mass detector, on an Agilent 7890A brand chromatograph with Agilent MS-5975C mass detector and Agilent 7683-B automatic injector, with HP-5MS capillary column.The antioxidant activity of peach seeds, through the Oracand Frap activity. The results show that the seed oil contains a high percentage of unsaturated fatty acids (91.6±2.65%), in which oleic, linoleic, palmitoleic acid and others stand out. The phenol content found was 93.8±2.24 mg GAE/100g, in relation to the Orac and Frap activity, the seed oil showed.